Peran dan Tantangan Guru dalam Pendidikan Inklusi - Ruth Agustaria; Yunita Lingga; Amelia Magdalena Sitorus; Samuel Hotasi Silalahi; Rahmilawati Ritonga (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
Inclusive education is an approach that emphasizes the importance of providing educational services for all children, including children with special needs (ABK), in a regular school environment. This concept is based on the philosophy that all students, regardless of physical, intellectual, social, or emotional differences, have the right to receive quality education. This study uses a literature review method by analyzing various sources to explore the role of teachers, challenges, and implementation of inclusive education in Indonesia. The results of the study indicate that teachers have a central role as facilitators, collaborators, motivators, and developers of adaptive curriculum. However, in practice, there are various challenges, such as lack of training, limited facilities, an inflexible curriculum, and social stigma against ABK. Therefore, it is necessary to strengthen teacher competence, increase policy support, and synergy between schools, families, and communities in realizing inclusive, fair, and quality education.